UMP Prihatin closes tie with Sungai Koyan community - Nor Salwana, Mohammad Idris (2022)
PAHANG, 24 August 2022 – Three days in Felda Sungai Koyan, Jerantut, provided sweet memories for 30 Universiti Malaysia Pahang (UMP) students who participated in Kembara UMP Prihatin with the Sungai Koyan Community recently.